Selling and marketing of R&D - Lever, O. William E. Jr.
O. William Lever, Jr. describes the key factors in selling R&D and the marketing principles and techniques that can help.
Both the tactical and strategic value of R&D to the business must be marketed and sold effectively if business investment in R&D is to be sustained.
Every day, R&D representatives are selling themselves, their results and their ideas. Recognizing and acknowledging this, along with developing the appropriate attributes of salesmanship, is critical to R&D success. Proactive initiatives to meet the needs of internal and external customers, and to become an integral and credible part of the business, enhance the impact and perceived value of R&D.
Keywords: Marketing--R&D.